On the irreversibility of Moore cellular automata over the ternary field and image application - Uguz, Selman; Akin, Hasan; Siap, Irfan; Sahin, Ugur (ELSEVIER SCIENCE INC, 2016)
Cellular automata have rich computational properties and provide many models in mathematical and physical processes. In this paper, one of the most commonly used neighborhood types of two dimensional (2D) cellular automata which is called the Moore neighborhood in two dimensional integer lattice is considered. We study the characterization of 2D linear cellular automata defined by the Moore neighborhood with periodic and null boundary conditions over ternary fields. Furthermore, we analyze some results of 2D cellular automata defined by the rule number 9840NB and finally also present applications to error correcting codes and image processing field. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Two-dimensional cellular automata; Moore neighborhood; Ternary fields; Reversibility; Error correcting codes; Image processing; CRYPTOGRAPHY; Engineering; Mathematics; Mechanics